Pierre Chambon, a pioneer of molecular biology and gene regulation in eukaryotes - Daniel Metzger (Proceedings of the National Academy of Sciences, 2026)
The scientific world has lost one of its great architects with the passing of Pierre Chambon, a visionary French scientist, institution builder, and demanding yet inspiring mentor. He provided major insights into the fundamental mechanisms governing gene expression and hormonal regulation that transformed modern biology and medicine. In addition, he developed groundbreaking mouse genetic techniques, and established Strasbourg as a leading European center for life sciences research. His death on May 5, 2026, at the age of 95, marks the end of an extraordinary era in science, yet his intellectual legacy will continue to shape generations of researchers across the world.